2022
DOI: 10.1111/iej.13798
|View full text |Cite
|
Sign up to set email alerts
|

Are electronic apex locators accurate in determining working length in primary teeth pulpectomies? A systematic review and meta‐analysis of clinical studies

Abstract: Background The lack of a well‐defined apical constriction in primary teeth raises concerns regarding the accuracy of electronic apex locators (EALs) for measuring working length. Objectives To evaluate the accuracy of EALs in determining working length in primary teeth pulpectomies. Methods Two reviewers searched ten databases up to September 2021. Clinical studies evaluating the accuracy of the electronic measurement of working length in primary teeth pulpectomies were included. Studies without a comparison g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The use of apex locators to determine the canal length of deciduous teeth is still a matter of debate. Although there are resources in the literature that do not recommend its use [ 59 ], resources that suggest its use but argue that there is not enough research on the subject [ 60 ], and resources that recommend its use [ 61 ] and references report that apex locators are much more acceptable by children than traditional radiography [ 62 ], no conclusive evidence has been provided as to which of the methods is the best.…”
Section: Discussionmentioning
confidence: 99%
“…The use of apex locators to determine the canal length of deciduous teeth is still a matter of debate. Although there are resources in the literature that do not recommend its use [ 59 ], resources that suggest its use but argue that there is not enough research on the subject [ 60 ], and resources that recommend its use [ 61 ] and references report that apex locators are much more acceptable by children than traditional radiography [ 62 ], no conclusive evidence has been provided as to which of the methods is the best.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the use of an electronic apex locator (EAL) eliminates these disadvantages [2]. It is stated that EALs can produce beneficial results, especially when radiographic imaging of the root apex is prevented by certain anatomical structures such as bone density, superposed tooth roots or zygomatic arch [3]. Unlike radiographic methods, by using the EAL the patient is not exposed to radiation, and the elimination of the time required to take a traditional film image are indicated as important advantages in the use of an EAL [4].…”
Section: Introductionmentioning
confidence: 99%